Evaluation of Lung Aeration and Respiratory System Mechanics in Obese Dogs Ventilated With Tidal Volumes Based on Ideal vs. Current Body Weight - Araos, Joaquin; Lacitignola, Luca; de Monte, Valentina; Stabile, Marzia; Porter, Ian; Hurtado, Daniel E.; Perez, Agustín; Crovace, Antonio; Grasso, Salvatore; Martin-Flores, Manuel; Staffieri, Francesco (Frontiers in Veterinary Science, 2021)
We describe the respiratory mechanics and lung aeration in anesthetized obese dogs ventilated with tidal volumes (VT) based on ideal (VTi) versus current (VTc) body weight. Six dogs with body condition scores ≥ 8/9 were included. End-expiratory respiratory mechanics and end-expiratory CT-scan were obtained at baseline for each dog. Thereafter, dogs were ventilated with VT 15 ml kg-1 based on VTi and VTc, applied randomly. Respiratory mechanics and CT-scan were repeated at end-inspiration during VTi and VTc. Data analyzed with linear mixed models and reported as mean ± SD or median [range]. Statistical significance p < 0.05. The elastance of the lung, chest wall and respiratory system indexed by ideal body weight (IBW) were positively correlated with body fat percentage, whereas the functional residual capacity indexed by IBW was negatively correlated with body fat percentage. At end-expiration, aeration (%) was: hyperaeration 0.03 [0.00 - 3.35], normoaeration 69.7 [44.6 – 82.2], hypoaeration 29.3 [13.6 – 49.4] and nonaeration (1.06% [0.37 – 6.02]. Next to the diaphragm, normoaeration dropped to 12 ± 11% and hypoaeration increased to 90 ± 8%. No differences in aeration between groups were found at end-inspiration. Airway driving pressure (cm H2O) was higher (p = 0.002) during VTc (9.8 ± 0.7) compared with VTi (7.6 ± 0.4). Lung strain was higher (p = 0.014) during VTc (55 ± 21%) than VTi (38 ± 10%). The stress index was higher (p = 0.012) during VTc (SI = 1.07 [0.14]) compared with VTi (SI = 0.93 [0.18]). This study indicates that body fat percentage influences the magnitude of lung, chest wall, and total respiratory system elastance and resistance, as well as functional residual capacity. Further, these results indicate that obese dogs have extensive areas of hypoaerated lungs, especially in caudodorsal regions. Finally, lung strain and airway driving pressure, surrogates of lung deformation, are higher during VTc than during VTi, suggesting that in obese anesthetized dogs, ventilation protocols based on IBW may be advantageous.